Efforts to Improve Student Financial Management Behavior through Lifestyle and Financial Knowledge and Financial Attitude - Khairatun Nazah; Maya Syahlina; Guliva Salsabila; Herlin Munthe; Nidya Banuari (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to analyze the effect of lifestyle, financial knowledge, and financial attitudes on financial management behavior. This research approach is quantitative. Collecting data using a questionnaire with a Likert scale. The population comes from 128 active Polytechnic Superior LP3M. The sampling technique used was total sampling where 128 students were used as research samples. The results showed that either partially or together lifestyle, financial knowledge, and financial attitudes have a positive and significant effect on finance management behavior in Politeknik Unggul LP3M Students. However, the variable with the strongest significance value in influencing finance management behavior in Politeknik Unggul LP3M Students is financial attitude.